Numerical study of pyrolysis oil combustion in an industrial gas turbine - Sallevelt, J.L.H.P.; Pozarlik, A.K.; Brem, G. (Energy conversion and management, 2016)
•The combustion of pyrolysis oil and ethanol in a gas turbine was modeled using CFD.•The multicomponent nature of pyrolysis oil was approximated using a discrete fuel model.•Comparative simulations were performed to evaluate different model settings.•Validation was performed with available outlet CO2 and temperature experimental data. The growing demand for the use of biofuels for decentralized power generation initiates new research in gas turbine technology. However, development of new combustors for low calorific fuels is costly in terms of time and money. To give momentum to biofuels application for power generation robust numerical models for multicomponent biofuels must be developed. This paper discusses the use of CFD techniques for modeling the combustion of pyrolysis oil in a new burner geometry from OPRA Turbines. Pyrolysis oil contains many different compounds, which are represented by a discrete fuel model consisting of seven components. The components and their initial fractions approximate the volatility, water content, elemental composition and heating value of a typical fast pyrolysis oil. Simulations have been carried out for both the multicomponent pyrolysis oil and, as a reference, ethanol, a single-component biofuel with a higher volatility. Comparative simulations have been performed to examine the influence of the initial droplet size and to evaluate different combustion models. The results were compared to available experimental data for pyrolysis oil and ethanol combustion. A qualitatively good agreement was achieved.